An Investigation into the Influence of Media Convergence on the Development of the Photography Sector - Tianyue, Tianyue (Transactions on Social Science, Education and Humanities Research, 2024)
The research examines the influence of media convergence on the development of the photographic industry. This analysis explores the rapid, simplified, and cost-effective evolution of photography, the impact on consumers and design, the appearance of novel photographers, and the potential challenges and obstacles associated with the rise of media in the photography sector. The research elucidates the impact of media convergence on the digital era, which is constantly inundated with content vying for individuals' attention. Media convergence has several advantages, such as the immediate availability of real-time material and news, the capacity for content providers to specifically target their desired audience through tailored content, the opportunity for the audience to also become content creators, and the cost-effectiveness of digital marketing, making it inexpensive and advantageous. The study examines the impact of media convergence on camera kinds, photograph types, and photographer profiles. The website design has been modified to enhance quick and effortless consumption by a public that is constantly bombarded with news, aiding them in selecting the information they prefer and desire.